Covalent modification of black phosphorus with alkoxy groups to improve the solubility and ambient stability - Zhao, Yun; Jiang, Yan; He, Menglu; Jiang, Gang; Zhu, Xuguang; Tian, Yue; Ni, Zhonghai (Nanoscale, 2021)
Black phosphorus (BP), a new 2D material as a layered allotrope of phosphorus, has regained attention due to its outstanding semiconductor characteristics. However, the major hurdles of using few-layer BP for applications are its poor solution processability and low ambient stability. Here, we report a covalent modification of BP nanosheets by a chemical reaction with sodium alkoxide. Fourier transform infrared spectra, Raman spectra, X-ray photoemission spectra and thermogravimetric analyses all confirmed the successful introduction of alkoxy groups on the BP surface with P-O-C bonds, which increased the solubility and ambient stability of BP. The introduced alkoxy groups as soluble side chains on the BP surface not only increase the solubility of BP nanosheets by almost 3 times, but also decrease the degradation ratio of the modified BP by about 2 times because of the encapsulation. In this work we developed a facile synthetic strategy to covalently modify BP by introducing soluble side chains, suggesting an effective way to realize its full potential application in electronics. This work develops a facile synthetic strategy to covalent modify of BP by introducing alkoxy groups as soluble side chains on the BP surface, which not only increases the solubility, but also inhibits the degradation because of the encapsulation.